2011
DOI: 10.1096/fj.11-190587
|View full text |Cite
|
Sign up to set email alerts
|

AMP‐activated protein kinase enhances the phagocytic ability of macrophages and neutrophils

Abstract: Although AMPK plays well-established roles in the modulation of energy balance, recent studies have shown that AMPK activation has potent anti-inflammatory effects. In the present experiments, we examined the role of AMPK in phagocytosis. We found that ingestion of Escherichia coli or apoptotic cells by macrophages increased AMPK activity. AMPK activation increased the ability of neutrophils or macrophages to ingest bacteria (by 46 ± 7.8 or 85 ± 26%, respectively, compared to control, P<0.05) and the ability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
118
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 119 publications
(129 citation statements)
references
References 58 publications
(87 reference statements)
10
118
1
Order By: Relevance
“…For example, AMPK activation was associated with enhanced T cell chemotaxis or migration of epithelial cells (38,50). AMPK activation has also been shown to enhance the phagocytic ability of macrophages, including uptake of bacteria, synthetic beads or apoptotic cells (39). These results are consistent with an ability of activated AMPK to facilitate microbial eradication through mechanisms that involve enhancement of neutrophil chemotaxis and/or bacterial uptake.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…For example, AMPK activation was associated with enhanced T cell chemotaxis or migration of epithelial cells (38,50). AMPK activation has also been shown to enhance the phagocytic ability of macrophages, including uptake of bacteria, synthetic beads or apoptotic cells (39). These results are consistent with an ability of activated AMPK to facilitate microbial eradication through mechanisms that involve enhancement of neutrophil chemotaxis and/or bacterial uptake.…”
Section: Discussionsupporting
confidence: 56%
“…Recent studies, including results obtained from our laboratory (39), have shown that metformin or other AMPK activators enhance cell mobility and also phagocytosis. For example, AMPK activation was associated with enhanced T cell chemotaxis or migration of epithelial cells (38,50).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations